A fiber-reinforced ceramic roller and a method for preparing the same

Through the preparation method of fiber-reinforced ceramic roller rod, the combination of silica fiber, aluminum sol composite material and alumina powder and other raw materials is used to generate a stable mullite fiber network structure, which solves the problem of low strength of traditional alumina ceramic roller rods. The problem of poor thermal shock resistance achieves higher strength and thermal shock resistance and extends service life.

CN119039028BActive Publication Date: 2025-02-25JIN GANG NEW MATERIALS +1

Patent Information

Application Number
CN202411533943.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

When traditional alumina ceramic roller rods operate in high-temperature kilns and other industrial equipment for a long time, they have low strength and poor thermal shock resistance, which cannot meet production requirements, resulting in short service life.

Method used

By using the preparation method of fiber-reinforced ceramic roller rod, silica fiber and aluminum sol are combined to form silica fiber-aluminum sol composite material, and mixed with alumina micro powder, kaolin, corundum sand and other raw materials, and then made by ball milling and spraying. Processes such as particle, vacuum extrusion molding, cold isostatic molding and high-temperature sintering to generate mullite fibers that are well-organized with the alumina matrix, forming an interlaced stable network structure, thereby improving the strength and thermal shock resistance of the roller rod .

Benefits of technology

It significantly improves the strength and thermal shock resistance of ceramic roller rods, extends the service life of high-temperature kilns, and meets the production requirements of industrial equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application discloses a fiber-reinforced ceramic roller and a preparation method thereof, and relates to the technical field of ceramic rollers. The present application firstly compounds silica fibers having a specific aspect ratio and length, and a nanoporous structure with aluminum sol to form a silica fiber-aluminum sol composite material, and then mixes it with other raw materials such as alumina micropowder, kaolin, corundum sand, a binder, a solvent, etc., and obtains an alumina ceramic mud material through ball milling, spray granulation, etc.; preforms an alumina ceramic roller green body through a vacuum extrusion molding process; prepares an alumina ceramic roller green body through a cold isostatic pressing secondary molding process, and further improves the green body strength; generates continuous mullite fibers through high-temperature sintering in-situ reaction to obtain a fiber-reinforced alumina ceramic roller, and the obtained ceramic roller mullite fibers have good bonding and good dispersibility with the alumina matrix, and have excellent strength, thermal shock resistance, etc., and have a longer service life in a high-temperature kiln.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic rollers, and in particular to a fiber-reinforced ceramic roller and a preparation method thereof. Background Art

[0002] Alumina ceramics have the characteristics of high hardness, wear resistance, and corrosion resistance, and have been widely used in the support and transmission devices of industrial equipment such as high-temperature kilns. The critical thermal shock temperature difference of alumina ceramics is only 200°C, and the thermal shock resistance is poor. When the temperature changes sharply, the alumina ceramic roller is easy to break. In addition, during the application of the kiln, the roller is subject to load for a long time, and the roller is prone to creep deformation, resulting in reduced transmission performance, which seriously affects the production efficiency of sintered products in the kiln. Therefore, improving the strength and thermal shock resistance of alumina ceramic rollers is crucial to extending their service life and ensuring stable production operation.

[0003] Fiber reinforcement is considered to be an effective way to improve the performance of alumina ceramics. The introduction of fibers can effectively disperse stress and prevent crack propagation, play a toughening role, thereby improving the strength and thermal shock resistance of ceramics. The fibers used for toughening are divided into oxide fibers and non-oxide fibers. Oxide fibers have stronger antioxidant properties than non-oxide fibers and are more widely used. Oxide fibers mainly include zirconia fibers, mullite fibers, alumina fibers, etc. Compared with other oxide fibers, mullite fibers have higher elastic modulus, high temperature stability and thermal expansion coefficient similar to alumina ceramics, and have become an important material for fiber-toughened alumina ceramics. In the process of mullite fiber toughening alumina ceramics, the surface treatment and dispersibility of the fibers are the most critical to the performance of ceramics. At present, some studies have used the external introduction method to mix mullite fibers and alumina raw materials. This process is simple and easy to prepare, but there are still problems such as poor interface compatibility between mullite fibers and alumina grains, weak interface bonding, and uneven dispersion. By in-situ generating mullite whiskers or fibers in the alumina ceramic matrix, a stable interface bonding between mullite and the alumina matrix can be achieved, reducing the interface stress concentration and the generation of cracks, forming a uniformly distributed mullite fiber network structure, thereby improving the strength and thermal shock resistance of alumina ceramics. However, the process of in-situ synthesis of mullite whiskers using this method will cause volume expansion, and the process control is difficult; the in-situ synthesis of mullite fibers (such as needle-shaped or rod-shaped) using this method requires a higher temperature and a longer insulation time, which is easy to produce more glass phases, but affects the strength of the roller. Rapid in-situ growth of mullite requires the introduction of a certain amount of mineralizer, and the calcifier is usually fluoride or chloride, such as CaF. Although the amount added per unit mass is not high, it forms a scale effect in industrial mass production and causes serious pollution. Summary of the invention

[0004] Based on the defects of the prior art, the purpose of this application is to provide a fiber-reinforced ceramic roller and a preparation method thereof, so as to effectively solve the problem that traditional alumina ceramic rollers have low strength and poor thermal shock resistance due to long-term operation in high-temperature kilns and other industrial equipment and cannot meet production requirements.

[0005] In order to achieve the above objectives, in a first aspect, the present application provides a method for preparing a fiber-reinforced ceramic roller, comprising the following steps:

[0006] The silica fiber, the aluminum sol and the dispersant are mixed and dispersed, and then dried for the first time to obtain a silica fiber-aluminum sol composite material;

[0007] The obtained silica fiber-alumina sol composite material is mixed with alumina micropowder, kaolin, corundum sand, a binder and a solvent, ball-milled and spray-granulated to obtain alumina ceramic mud;

[0008] The obtained alumina ceramic mud is sequentially subjected to vacuum extrusion molding, drying, cold isostatic pressing molding and sintering to obtain a fiber-reinforced ceramic roller;

[0009] The silica fiber has an average aspect ratio of 50-200, an average length of 49-81 μm, and a nanoporous structure.

[0010] The present application first compounds silica fibers having a specific average aspect ratio and average length, as well as a nanoporous structure, with aluminum sol to form a silica fiber-aluminum sol composite material, and then mixes it with other raw materials such as alumina powder, kaolin, corundum sand, a binder, a solvent, etc., so that during the sintering process, the silica fibers and the aluminum sol in the silica fiber-aluminum sol composite material preferentially react to form nuclei, inducing the silica fibers and the alumina components in the roller to react quickly to generate mullite fibers with good bonding with the alumina matrix, ensuring that the mullite fibers are well dispersed in the matrix and improving the interface stability between the mullite and the matrix; in addition, flaky mullite and needle-shaped secondary mullite can be formed by the reaction of kaolin and alumina powder, forming a mutually interlaced stable network structure inside the ceramic, thereby enhancing the strength and thermal shock resistance of the roller.

[0011] The applicant found in the research process that the microscopic shape, microstructure, average aspect ratio, average length, etc. of silica will significantly affect the toughening effect. Only by selecting silica fibers with nanoporous structure and controlling their average aspect ratio and average length within the above range, the toughening and improvement of thermal shock resistance can be better. The microstructure of silica is fibrous, which is conducive to the production of fibrous mullite. Fibrous mullite can play a bridging toughening role in the ceramic matrix, bear part of the external stress, and consume energy by pulling out, debonding and breaking to prevent the expansion of cracks, so as to achieve the purpose of improving the strength and toughness of the material; the nanoporous structure is conducive to the infiltration of nano-alumina, increase the local aluminum concentration, and promote the growth of mullite fibers; the average aspect ratio and average length are controlled within a suitable range, which can avoid fiber damage caused by ball milling, while being conducive to the dispersion of silica and reducing agglomeration, thereby helping to improve the toughening effect.

[0012] The average aspect ratio of the silica fibers is 50-200, such as 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, or a range formed by any two of the above values.

[0013] The average length of the silica fibers is 49-81 μm, such as 50 μm, 52 μm, 55 μm, 57 μm, 60 μm, 62 μm, 65 μm, 67 μm, 70 μm, 72 μm, 75 μm, 77 μm, 80 μm, or a range formed by any two of the above values.

[0014] Preferably, the purity of the silica fiber is ≥3N. By controlling the purity of the silica fiber to be ≥3N, such as 3N or 4N, the introduction of impurities can be reduced and the performance of the ceramic roller can be improved. The purity of the silica fiber can be measured according to the following method: the purity test is performed using the industry standard YS / T 1160-2016, wherein the light tube current is 38mA, the light tube voltage is 35kV, the divergence slit is 0.5°, the time constant is 10, the scanning speed is 0.25° / min, the scanning step is 0.03°, and the comprehensive stability is 0.05%.

[0015] Preferably, the average diameter of the silica fiber is 0.4-1 μm. The average diameter of the silica fiber can be selected to be 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, or a range formed by any two of the above values.

[0016] The average length, average diameter and average aspect ratio of the silica fibers can be measured according to the following method: using Image J software, randomly selecting at least 100 fibers from an electron microscope image of silica fibers, performing statistical analysis on the lengths, diameters or aspect ratios of these fibers, and determining their average values.

[0017] Preferably, the silica fibers are in a glassy state.

[0018] Preferably, the method for preparing the silica fiber comprises the following steps: firstly, -3 Pa and heating conditions, the elemental silicon is melted, then filled with inert protective gas until the pressure is 100-260Pa, the temperature is continued to rise to form silicon vapor from the molten silicon, oxygen is then introduced and the pressure is maintained at 100-260Pa, the temperature is kept to react for 1-10 hours, and after the reaction is completed, the silicon dioxide fiber is obtained by cooling. Argon can be selected as the inert protective gas.

[0019] Preferably, the weight ratio of the oxygen intake to elemental silicon is 1-2:1.

[0020] Preferably, the melting temperature of the elemental silicon is ≥1410° C. Exemplarily, the melting temperature of the elemental silicon is 1410-1600° C.

[0021] Preferably, the temperature at which the molten silicon forms silicon vapor is ≥ 1700° C. Exemplarily, the temperature at which the molten silicon forms silicon vapor is 1700° C. to 1800° C.

[0022] Preferably, the heating rate of the continued heating is 3-8°C / min.

[0023] Preferably, in the silica fiber-alumina sol composite material, the weight ratio of alumina to silica fiber is (1.9-4.1):1, such as 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4:1, or a range formed by any two of the above values. More preferably, in the silica fiber-alumina sol composite material, the weight ratio of alumina to silica fiber is (2.6-3.1):1.

[0024] When the weight ratio of alumina to silica fiber in the silica fiber-alumina sol composite material is in the range of (1.9-4.1):1, especially in the range of (2.6-3.1):1, it is more conducive to the stable growth of the mullite fiber network of silica fiber and alumina, thereby improving the strength and thermal shock resistance of the roller.

[0025] The weight ratio of alumina to silica fiber in the silica fiber-alumina sol composite material=the weight of alumina in the alumina sol / the weight of silica fiber used.

[0026] Preferably, the weight of the dispersant is 0.1% to 1% of the total weight of the silica fiber and the alumina sol, such as 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or a range formed by any two of the above values. More preferably, the weight of the dispersant is 0.4% to 0.7% of the total weight of the silica fiber and the alumina sol.

[0027] When the weight of the dispersant is 0.1% to 1%, especially 0.4% to 0.7%, of the total weight of the silica fiber and the aluminum sol, the formed dispersion system is more uniform and stable, which is conducive to more uniform adhesion of nano-alumina to the surface of the silica fiber, making the roller stronger and more resistant to thermal shock.

[0028] Preferably, the raw materials for preparing the alumina ceramic mud include the following components by weight: 20-40 parts of alumina powder, 15-30 parts of kaolin, 10-20 parts of the silica fiber-alumina sol, 1-5 parts of a binder, 30-50 parts of corundum sand, and 15-25 parts of a solvent, which is more conducive to the formation of needle-shaped or rod-shaped mullite and the densification of the roller, and the glass phase content is more appropriate, so that the strength and thermal shock resistance of the roller are better. Among them,

[0029] The amount of alumina powder can be selected to be 20 parts by weight, 22 parts by weight, 24 parts by weight, 26 parts by weight, 28 parts by weight, 30 parts by weight, 32 parts by weight, 34 parts by weight, 36 parts by weight, 38 parts by weight, 40 parts by weight, or a range formed by any two of the above values;

[0030] The amount of kaolin can be selected to be 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 22 parts by weight, 24 parts by weight, 26 parts by weight, 28 parts by weight, 30 parts by weight, or a range formed by any two of the above values;

[0031] The amount of the silica fiber-alumina sol can be selected to be 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, or a range formed by any two of the above values;

[0032] The amount of the binder can be selected to be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, or a range formed by any two of the above values;

[0033] The amount of corundum sand can be selected to be 30 parts by weight, 32 parts by weight, 34 parts by weight, 36 parts by weight, 38 parts by weight, 40 parts by weight, 42 parts by weight, 44 parts by weight, 46 parts by weight, 48 parts by weight, 50 parts by weight, or a range formed by any two of the above values;

[0034] The amount of solvent used can be selected to be 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, or a range formed by any two of the above values.

[0035] More preferably, the weight of the corundum sand is 0.49 to 0.71 times the total weight of the alumina powder, the kaolin, the silica fiber-alumina sol and the binder, such as 0.5 times, 0.55 times, 0.6 times, 0.65 times, 0.7 times, or a range formed by any two of the above values. The aggregate supporting effect is stronger, the phenomenon of hanging sintering and breaking of the rod is avoided, and the strength and thermal shock resistance of the roller are better.

[0036] More preferably, the weight ratio of the alumina powder to the kaolin is (0.79-1.21):1, such as 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1 or a range formed by any two of the above values, which is more conducive to forming a stable mullite network and making the roller have better strength and thermal shock resistance.

[0037] More preferably, the weight of the alumina powder is more than 14% of the total weight of the raw materials for preparing the alumina ceramic mud, such as 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36% or a range formed by any two of the above values.

[0038] Preferably, the dispersant includes but is not limited to at least one of polycarboxylic acid amine, sodium polyacrylate, methyl cellulose and polyvinyl alcohol.

[0039] Preferably, the binder is an organic binder, including but not limited to at least one of phenolic resin, polyvinyl pyrrolidone and carboxymethyl cellulose.

[0040] Preferably, the solvent comprises water.

[0041] Preferably, the vacuum degree of the vacuum extrusion molding is 0.01-0.09 MPa, and the extrusion force is 5-30 MPa.

[0042] Preferably, the cold isostatic pressing pressure is 120-240 MPa, and the holding time is 10-60 s.

[0043] Preferably, the temperature of the drying (i.e., the drying between the vacuum extrusion molding and the cold isostatic pressing molding) is 60-120° C., and the time of the drying (i.e., the drying between the vacuum extrusion molding and the cold isostatic pressing molding) is 12-48 hours.

[0044] Preferably, the sintering is hanging sintering, the sintering temperature is 1400-1800° C., and the holding time is 5-10 hours.

[0045] In a second aspect, the present application provides a fiber-reinforced ceramic roller produced by the preparation method.

[0046] Compared with the prior art, the beneficial effects of this application are:

[0047] (1) In the present application, silica fibers having a specific average aspect ratio and average length and a nanoporous structure are firstly compounded with aluminum sol to form a silica fiber-aluminum sol composite material, and then mixed with other raw materials such as alumina micropowder, kaolin, corundum sand, a binder, a solvent, etc., and alumina ceramic mud is obtained by ball milling, spray drying, etc.; alumina ceramic roller green body is prefabricated by vacuum extrusion molding process; alumina ceramic roller green body is prepared by cold isostatic pressing secondary molding process to further improve the green body strength; continuous molybdenum is generated by high temperature sintering in situ reaction The fiber-reinforced alumina ceramic roller is obtained by sintering silica fibers. During the high-temperature sintering process, local silica fibers and alumina sol in the silica fiber-alumina sol composite material preferentially react to form nuclei, inducing a rapid reaction between the silica fibers and the alumina components in the roller, growing mullite fibers that are well combined with the matrix, ensuring that the mullite fibers are well dispersed in the matrix. In addition, flaky mullite and needle-shaped secondary mullite can be formed through the action of kaolin and alumina micropowder, forming a mutually interlaced stable network structure inside the ceramic, thereby enhancing the strength and thermal shock resistance of the roller.

[0048] (2) Compared with directly introducing mullite fibers, the fiber-reinforced ceramic roller of the present application can achieve stable interface bonding between mullite and alumina matrix by in-situ growing mullite fibers, reduce interface stress concentration and crack generation, thereby improving the strength and thermal shock resistance of the alumina ceramic roller and extending its service life in high-temperature kilns. DETAILED DESCRIPTION

[0049] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.

[0050] Unless otherwise specified, the following examples and comparative examples all use commercially available raw materials.

[0051] Example 1

[0052] This embodiment provides a method for preparing a fiber-reinforced ceramic roller, comprising the following steps:

[0053] Weigh 5 kg of silicon and place it in the vacuum furnace reaction chamber, evacuate to a vacuum degree of 10 -5 Pa, and heated to 1500℃ at a heating rate of 5℃ / min to completely melt the elemental silicon; then introduced 5N argon to 200Pa, and continued to heat to 1700℃ to completely transform the molten silicon into silicon vapor, introduced 7.5kg oxygen and maintained the pressure at 200Pa (when the pressure is greater than 200Pa, release the pressure to ensure that the pressure is maintained at 200Pa), and kept the temperature for 6h to obtain silica fiber;

[0054] 19 kg of silica fiber and 56 kg of alumina sol powder were added to 100 kg of water, and 0.5 kg of polycarboxylic acid amine was added as a dispersant, and the mixture was stirred for 3 h, and then dried at 300 °C for 7 h to obtain a silica-alumina sol composite material, wherein the weight ratio of alumina to silica fiber in the obtained silica-alumina sol composite material was 2.95:1;

[0055] The obtained 13kg silica-alumina sol composite material was ball-milled with 25kg alumina powder, 25kg kaolin, 40kg corundum sand, 2kg binder phenolic resin and 20kg solvent water, and spray granulated to obtain alumina ceramic mud;

[0056] The obtained alumina ceramic mud is subjected to vacuum extrusion molding, wherein the vacuum degree is 0.05 MPa and the extrusion force is 15 MPa, to obtain a first alumina ceramic green body;

[0057] The first alumina ceramic green body is subjected to cold isostatic pressing at a pressure of 150 MPa and a holding time of 30 seconds to obtain a second alumina ceramic green body;

[0058] The obtained second alumina ceramic green body was dried at 100° C. for 24 hours to obtain a third alumina ceramic green body;

[0059] The obtained third alumina ceramic green body was sintered in a high-temperature kiln at a temperature of 1600° C. for 10 hours to obtain a fiber-reinforced alumina ceramic roller.

[0060] Example 2

[0061] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Example 1 as follows: 25 kg of silica fiber, 50 kg of alumina sol dry powder, and 0.5 kg of dispersant polycarboxylic acid amine are used in preparing the silica fiber-alumina sol composite material, and the weight ratio of alumina to silica fiber in the obtained silica fiber-alumina sol composite material is 2:1; in addition, in the process of preparing alumina ceramic mud from the silica fiber-alumina sol composite material, the amount of each raw material remains unchanged.

[0062] Example 3

[0063] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Embodiment 1 as follows: 15 kg of silica fiber, 60 kg of alumina sol dry powder, and 0.5 kg of dispersant polycarboxylic acid amine are used in preparing the silica fiber-alumina sol composite material, and the weight ratio of alumina to silica fiber in the obtained silica fiber-alumina sol composite material is 4:1; in addition, in the process of preparing alumina ceramic mud from the silica fiber-alumina sol composite material, the amount of each raw material remains unchanged.

[0064] Example 4

[0065] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Example 1 as follows: 37.5 kg of silica fiber, 37.5 kg of alumina sol dry powder, and 0.5 kg of dispersant polycarboxylic acid amine are used in preparing the silica fiber-alumina sol composite material, and the weight ratio of alumina to silica fiber in the obtained silica fiber-alumina sol composite material is 1:1; in addition, in the process of preparing alumina ceramic mud from the silica fiber-alumina sol composite material, the amount of each raw material remains unchanged.

[0066] Example 5

[0067] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Embodiment 1 as follows: 12.5 kg of silica fiber, 62.5 kg of alumina sol dry powder, and 0.5 kg of dispersant polycarboxylic acid amine are used in preparing the silica fiber-alumina sol composite material, and the weight ratio of alumina to silica fiber in the obtained silica fiber-alumina sol composite material is 5:1; in addition, in the process of preparing alumina ceramic mud from the silica fiber-alumina sol composite material, the amount of each raw material remains unchanged.

[0068] Example 6

[0069] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Example 1 as follows: 19 kg of silica fiber, 56 kg of alumina sol dry powder, and 0.075 kg of dispersant polycarboxylic acid amine are used in preparing the silica fiber-alumina sol composite material, and the weight ratio of alumina to silica fiber in the obtained silica fiber-alumina sol composite material is 2.95:1; in addition, in the process of preparing alumina ceramic mud from the silica fiber-alumina sol composite material, the amount of each raw material remains unchanged.

[0070] Example 7

[0071] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Example 1 as follows: 19 kg of silica fiber, 56 kg of alumina sol dry powder, and 0.75 kg of dispersant polycarboxylic acid amine are used in preparing the silica fiber-alumina sol composite material, and the weight ratio of alumina to silica fiber in the obtained silica fiber-alumina sol composite material is 2.95:1; in addition, in the process of preparing alumina ceramic mud from the silica fiber-alumina sol composite material, the amount of each raw material remains unchanged.

[0072] Example 8

[0073] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Example 1 as follows: 19 kg of silica fiber, 56 kg of alumina sol dry powder, and 0.05 kg of dispersant polycarboxylic acid amine are used in preparing the silica fiber-alumina sol composite material, and the weight ratio of alumina to silica fiber in the obtained silica fiber-alumina sol composite material is 2.95:1; in addition, in the process of preparing alumina ceramic mud from the silica fiber-alumina sol composite material, the amount of each raw material remains unchanged.

[0074] Example 9

[0075] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Example 1 as follows: 19 kg of silica fiber, 56 kg of alumina sol dry powder, and 0.9 kg of dispersant polycarboxylic acid amine are used in preparing the silica fiber-alumina sol composite material, and the weight ratio of alumina to silica fiber in the obtained silica fiber-alumina sol composite material is 2.95:1; in addition, in the process of preparing alumina ceramic mud from the silica fiber-alumina sol composite material, the amount of each raw material remains unchanged.

[0076] Example 10

[0077] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of the various raw materials used in preparing the alumina ceramic mud are different, specifically 14 kg of silica-alumina sol composite material, 26.92 kg of alumina powder, 26.92 kg of kaolin, 35 kg of corundum sand, 2.15 kg of binder phenolic resin and 20 kg of solvent water.

[0078] Embodiment 11

[0079] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Embodiment 1 as follows: the amounts of the various raw materials used in preparing the alumina ceramic mud are different, specifically 12.35 kg of silica-alumina sol composite material, 23.76 kg of alumina powder, 23.76 kg of kaolin, 43.23 kg of corundum sand, 1.9 kg of binder phenolic resin and 20 kg of solvent water.

[0080] Example 12

[0081] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Example 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 15 kg of silica-alumina sol composite material, 28.85 kg of alumina micropowder, 28.85 kg of kaolin, 30 kg of corundum sand, 2.31 kg of binder phenolic resin and 20 kg of solvent water.

[0082] Example 13

[0083] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Embodiment 1 as follows: the amounts of the various raw materials used in preparing the alumina ceramic mud are different, specifically 11.67 kg of silica-alumina sol composite material, 22.43 kg of alumina micropowder, 22.43 kg of kaolin, 46.67 kg of corundum sand, 1.79 kg of binder phenolic resin and 20 kg of solvent water.

[0084] Embodiment 14

[0085] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 20kg of alumina micropowder, 30kg of kaolin, 40kg of corundum sand, 2kg of binder phenolic resin and 20kg of solvent water.

[0086] Embodiment 15

[0087] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Example 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 22.22kg of alumina micropowder, 27.78kg of kaolin, 40kg of corundum sand, 2kg of binder phenolic resin and 20kg of solvent water.

[0088] Example 16

[0089] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of the various raw materials used in preparing the alumina ceramic mud are different, specifically 13 kg of silica-alumina sol composite material, 27.27 kg of alumina micropowder, 22.73 kg of kaolin, 40 kg of corundum sand, 2 kg of binder phenolic resin and 20 kg of solvent water.

[0090] Embodiment 17

[0091] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 30kg of alumina micropowder, 20kg of kaolin, 40kg of corundum sand, 2kg of binder phenolic resin and 20kg of solvent water.

[0092] Embodiment 18

[0093] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 20kg of silica-alumina sol composite material, 40kg of alumina micropowder, 30kg of kaolin, 30kg of corundum sand, 5kg of binder phenolic resin and 25kg of solvent water.

[0094] Embodiment 19

[0095] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 10kg of silica-alumina sol composite material, 20kg of alumina micropowder, 15kg of kaolin, 50kg of corundum sand, 1kg of binder phenolic resin and 15kg of solvent water.

[0096] Embodiment 20

[0097] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 15kg of alumina micropowder, 25kg of kaolin, 40kg of corundum sand, 2kg of binder phenolic resin and 20kg of solvent water.

[0098] Embodiment 21

[0099] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 60kg of alumina micropowder, 25kg of kaolin, 40kg of corundum sand, 2kg of binder phenolic resin and 20kg of solvent water.

[0100] Embodiment 22

[0101] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 25kg of alumina micropowder, 10kg of kaolin, 40kg of corundum sand, 2kg of binder phenolic resin and 20kg of solvent water.

[0102] Embodiment 23

[0103] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of the various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 25kg of alumina micropowder, 40kg of kaolin, 40kg of corundum sand, 2kg of binder phenolic resin and 20kg of solvent water.

[0104] Embodiment 24

[0105] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Example 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 25kg of alumina powder, 25kg of kaolin, 20kg of corundum sand, 2kg of binder phenolic resin and 20kg of solvent water.

[0106] Embodiment 25

[0107] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 25kg of alumina powder, 25kg of kaolin, 75kg of corundum sand, 2kg of binder phenolic resin and 20kg of solvent water.

[0108] Embodiment 26

[0109] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 25kg of alumina powder, 25kg of kaolin, 40kg of corundum sand, 0.5kg of binder phenolic resin and 20kg of solvent water.

[0110] Embodiment 27

[0111] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Embodiment 1 as follows: the amounts of various raw materials used in preparing the alumina ceramic mud are different, specifically 13kg of silica-alumina sol composite material, 25kg of alumina micropowder, 25kg of kaolin, 40kg of corundum sand, 8kg of binder phenolic resin and 20kg of solvent water.

[0112] Embodiment 28

[0113] This embodiment provides a method for preparing a fiber-reinforced ceramic roller, comprising the following steps:

[0114] Weigh 5 kg of silicon and place it in the vacuum furnace reaction chamber, evacuate to a vacuum degree of 10 -2 Pa, and heated to 1410℃ at a heating rate of 3℃ / min to completely melt the elemental silicon; then introduced 5N argon to 100Pa, and continued to heat to 1700℃ to completely transform the molten silicon into silicon vapor, introduced 7.5kg oxygen and maintained the pressure at 100Pa (when the pressure is greater than 100Pa, release the pressure to ensure that the pressure is maintained at 100Pa), and kept the temperature for 10h to obtain silica fiber;

[0115] 19 kg of the obtained silica fiber was added to 56 kg of alumina sol dry powder, and 0.5 kg of dispersant sodium polyacrylate was added, stirred for 3 hours, and then dried at 400° C. for 10 hours to obtain a silica-alumina sol composite material, wherein the weight ratio of alumina to silica fiber in the obtained silica-alumina sol composite material was 2.95:1;

[0116] The obtained 13kg silica-alumina sol composite material was ball-milled with 25kg alumina powder, 25kg kaolin, 40kg corundum sand, 2kg binder polypyrrolidone and 20kg solvent water, and spray granulated to obtain alumina ceramic mud;

[0117] The obtained alumina ceramic mud is subjected to vacuum extrusion molding, wherein the vacuum degree is 0.01 MPa and the extrusion force is 30 MPa, to obtain a first alumina ceramic green body;

[0118] The obtained first alumina ceramic green body is subjected to cold isostatic pressing at a pressure of 120 MPa and a holding time of 60 seconds to obtain a second alumina ceramic green body;

[0119] The obtained second alumina ceramic green body was dried at 60° C. for 48 hours to obtain a third alumina ceramic green body;

[0120] The obtained third alumina ceramic green body was sintered in a high-temperature kiln at a temperature of 1400° C. for 10 hours to obtain a fiber-reinforced alumina ceramic roller.

[0121] Embodiment 29

[0122] This embodiment provides a method for preparing a fiber-reinforced ceramic roller, comprising the following steps:

[0123] Weigh 20 kg of silicon and place it in the vacuum furnace reaction chamber, evacuate to a vacuum degree of 10 -7 Pa, and the temperature was raised to 1600℃ at a heating rate of 8℃ / min to completely melt the elemental silicon; then 5N argon was introduced to 260Pa, and the temperature was continued to be raised to 1700℃ to completely transform the molten silicon into silicon vapor, and 7.5kg oxygen was introduced and the pressure was maintained at 260Pa (when the pressure was greater than 260Pa, the pressure was released to ensure that the pressure was maintained at 260Pa), and the reaction was kept warm for 1h to obtain silica fiber;

[0124] 19 kg of the prepared silica fiber was added to 56 kg of alumina sol dry powder, and 0.5 kg of dispersant methyl cellulose was added, stirred for 3 hours, and then dried at 800°C for 5 hours to obtain a silica-alumina sol composite material, wherein the weight ratio of alumina to silica fiber in the obtained silica-alumina sol composite material was 2.95:1;

[0125] The obtained 13kg silica-alumina sol composite material was ball-milled with 25kg alumina powder, 25kg kaolin, 40kg corundum sand, 2kg binder carboxymethyl cellulose and 20kg solvent water, and spray granulated to obtain alumina ceramic mud;

[0126] The obtained alumina ceramic mud is subjected to vacuum extrusion molding, wherein the vacuum degree is 0.09 MPa and the extrusion force is 5 MPa to obtain a first alumina ceramic green body;

[0127] The obtained first alumina ceramic green body is subjected to cold isostatic pressing at a pressure of 240 MPa and a holding time of 10 seconds to obtain a second alumina ceramic green body;

[0128] The obtained second alumina ceramic green body was dried at 120° C. for 12 hours to obtain a third alumina ceramic green body;

[0129] The obtained third alumina ceramic green body was sintered in a high temperature kiln at a temperature of 1800° C. for 5 hours to obtain a fiber reinforced alumina ceramic roller.

[0130] Embodiment 30

[0131] The present embodiment provides a method for preparing a fiber-reinforced ceramic roller, which differs from Embodiment 1 in that the amounts of the raw materials used in preparing the silica fiber are different, specifically, 5 kg of elemental silicon is used in preparing the silica fiber, 6.25 kg of oxygen is introduced, and the weight ratio of oxygen introduction to elemental silicon is 1.25:1.

[0132] Embodiment 31

[0133] This embodiment provides a method for preparing a fiber-reinforced ceramic roller, which is different from Example 1 as follows: the amounts of various raw materials used in preparing the silica fiber are different, specifically, 5 kg of elemental silicon is used in preparing the silica fiber, 5 kg of oxygen is introduced, and the weight ratio of oxygen introduction to elemental silicon is 1:1.

[0134] Comparative Example 1

[0135] This comparative example provides a method for preparing a fiber-reinforced ceramic roller, which is different from Example 1 in that an equal weight of spherical silica (Yumu New Materials, model YM-SiO2-500) is used to completely replace the silica fiber, and the silica fiber is not prepared.

[0136] Comparative Example 2

[0137] This comparative example provides a method for preparing a fiber-reinforced ceramic roller, which is different from Example 1 as follows: an equal weight of silicon dioxide having a nanoporous structure (Yumu New Materials, model YM-SiO2-ZKW01) is used to completely replace the silicon dioxide fiber.

[0138] Comparative Example 3

[0139] This comparative example provides a method for preparing a fiber-reinforced ceramic roller, which is different from Example 1 as follows: short silica fibers (Tai'an glass fiber, model EMG10-35) with an aspect ratio of 10 are used to completely replace the silica fibers.

[0140] Comparative Example 4

[0141] This comparative example provides a method for preparing a fiber-reinforced ceramic roller, which is different from Example 1 as follows: silica long fibers (Tai'an glass fiber, model HMG443R) with an aspect ratio of 300 are used to completely replace the silica fibers.

[0142] Comparative Example 5

[0143] This comparative example provides a method for preparing a fiber-reinforced ceramic roller, which differs from Example 1 as follows: In the process of preparing alumina ceramic mud using silica fiber, the silica fiber, aluminum sol and dispersant are mixed and dispersed, and then directly mixed and dispersed with kaolin, corundum sand, a binder and a solvent, and spray dried to obtain alumina ceramic mud.

[0144] Comparative Example 6

[0145] This comparative example provides a method for preparing a fiber-reinforced ceramic roller, which differs from Example 1 as follows: in the process of preparing alumina ceramic mud using silica fiber, the silica fiber is mixed and dispersed with alumina powder, kaolin, corundum sand, a binder and a solvent, and then aluminum sol and a dispersant are added to mix and disperse, and spray dried to obtain alumina ceramic mud.

[0146] The fiber-reinforced alumina ceramic rollers with an outer diameter of 60 mm, a thickness of 10 mm and a length of 3000 mm were prepared by the above-mentioned example and comparative example preparation methods, and the following performance tests were performed:

[0147] Room temperature flexural strength: GB / T 6569-1986, tested by three-point bending method, 25°C;

[0148] Thermal shock resistance: YB / T 376.2-1995, sample preheating temperature is 300℃, sample preheating temperature is 2h, heating furnace temperature is 1300℃.

[0149] The test results are shown in Table 1.

[0150] Table 1

[0151]

[0152] It can be seen from the above data that the room temperature flexural strength of the ceramic rollers obtained in the embodiments of the present application is above 118 MPa, and the number of thermal shock resistance cycles is above 11 times.

[0153] From the comparison of Examples 1 to 5, it can be seen that when the weight ratio of alumina to silica fiber in the silica fiber-alumina sol composite material is in the range of (1.9~4.1):1, the room temperature flexural strength and thermal shock resistance of the roller are better. This is because when the weight ratio is in the above range, it is conducive to the formation of mullite fiber.

[0154] From the comparison of Examples 1 and 6 to 9, it can be seen that when the weight of the dispersant is 0.1% to 1% of the total weight of the silica fiber and the aluminum sol, the room-temperature flexural strength and thermal shock resistance of the roller are better. This is because the formed dispersion system is more uniform and stable and not easy to agglomerate.

[0155] From the comparison of Examples 1 and 10 to 13, it can be seen that when the weight of corundum sand is 0.49 to 0.71 times the total weight of alumina powder, kaolin, silica fiber-alumina sol and binder, that is, when the weight of aggregate is 0.49 to 0.71 times the total weight of matrix material, the room-temperature flexural strength and thermal shock resistance of the roller are better. This is because the sintering temperature is more suitable and the aggregate can play a stronger supporting role.

[0156] From the comparison of Examples 1 and 14 to 17, it can be seen that when the weight ratio of alumina powder to kaolin is (0.79 to 1.21):1, the room temperature flexural strength and thermal shock resistance of the roller are better. This is because the interface bonding between mullite and the alumina matrix is ​​more stable.

[0157] From the comparison of Examples 1 and 18 to 27, it can be seen that when the raw materials for preparing the alumina ceramic mud include the following components in parts by weight: 20 to 40 parts of alumina micropowder, 15 to 30 parts of kaolin, 10 to 20 parts of the silica fiber-alumina sol, 1 to 5 parts of a binder, 30 to 50 parts of corundum sand, and 15 to 25 parts of a solvent, the room-temperature flexural strength and thermal shock resistance of the roller are better. This is because it is more conducive to the formation of needle-shaped or rod-shaped mullite and the densification of the roller.

[0158] From the comparison between Examples 1 and 30-31, it can be seen that when the purity of the silica fiber is ≥3N, the strength and thermal shock resistance of the roller are better because less impurities are introduced.

[0159] In Comparative Examples 1 to 4, the microscopic shape of the silicon dioxide is not fibrous, does not have a pore structure, or the aspect ratio or length is too high or too low, resulting in deviations in the flexural strength and thermal shock resistance of the ceramic materials.

[0160] The deviation in room temperature flexural strength and thermal shock resistance of the ceramic material in Comparative Example 5 is because in the process of preparing alumina ceramic mud using silica fiber, the silica fiber, aluminum sol and dispersant are mixed and dispersed without drying treatment, but are mixed with other raw materials, resulting in agglomeration and poor dispersibility.

[0161] The deviation in room temperature flexural strength and thermal shock resistance of the ceramic material in Comparative Example 6 is because in the process of preparing alumina ceramic mud using silica fibers, the silica fibers are not first made into silica fiber-alumina sol composite materials, resulting in a deviation in the bonding between the mullite and the alumina matrix in the ceramic roller.

[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A method for preparing a fiber-reinforced ceramic roller, characterized in that: The following steps are involved: The silica fiber, the aluminum sol and the dispersant are mixed and dispersed, and then dried for the first time to obtain a silica fiber-aluminum sol composite material; The obtained silica fiber-alumina sol composite material is mixed with alumina micropowder, kaolin, corundum sand, a binder and a solvent, ball-milled and spray-granulated to obtain alumina ceramic mud; The obtained alumina ceramic mud is sequentially subjected to vacuum extrusion molding, drying, cold isostatic pressing molding and sintering to obtain a fiber-reinforced ceramic roller; The silica fibers have an average aspect ratio of 50 to 200, an average length of 49 to 81 μm, and a nanoporous structure; In the silica fiber-alumina sol composite material, the weight ratio of alumina to silica fiber is (1.9-4.1):1, and the weight of the dispersant is 0.1%-1% of the total weight of the silica fiber and the alumina sol; The raw materials for preparing the alumina ceramic mud include the following components in parts by weight: 20-40 parts of alumina powder, 15-30 parts of kaolin, 10-20 parts of the silica fiber-alumina sol, 1-5 parts of a binder, 30-50 parts of corundum sand, and 15-25 parts of a solvent.

2. The method for preparing a fiber-reinforced ceramic roller according to claim 1, characterized in that: The purity of the silica fiber is ≥3N.

3. The method for preparing a fiber-reinforced ceramic roller according to claim 2, characterized in that: The purity of the silica fiber is 3N~4N.

4. The method for preparing a fiber-reinforced ceramic roller according to claim 1, characterized in that: The silica fiber also satisfies at least one of the following conditions: S1, the average diameter of the silica fiber is 0.4~1μm; S2. The silica fiber is in a glassy state.

5. The method for preparing a fiber-reinforced ceramic roller according to claim 1, characterized in that: At least one of the following conditions is met: S3, the weight of the corundum sand is 0.49 to 0.71 times the total weight of the alumina powder, the kaolin, the silica fiber-alumina sol and the binder; S4. The weight ratio of the alumina powder to the kaolin is (0.79~1.21):

1.

6. The method for preparing a fiber-reinforced ceramic roller according to claim 1, characterized in that: The preparation method of the silica fiber comprises the following steps: firstly -3 The silicon dioxide fiber is prepared by melting the silicon element under the conditions of 100-260 Pa and heating, then introducing an inert protective gas to a pressure of 100-260 Pa, continuing to increase the temperature to form silicon vapor from the molten silicon, introducing oxygen and maintaining the pressure at 100-260 Pa, and keeping the temperature for reaction for 1-10 hours. After the reaction is completed, cooling is performed to obtain the silicon dioxide fiber.

7. The method for preparing a fiber-reinforced ceramic roller according to claim 6, characterized in that: The method for preparing the silica fiber also satisfies at least one of the following conditions: S5, the weight ratio of the oxygen intake to the elemental silicon is 1-2:1; S6, the melting temperature of the elemental silicon is ≥1410°C; S7, the temperature of the molten silicon to form silicon vapor is ≥1700°C; S8. The heating rate of the continued heating is 3-8°C / min.

8. The method for preparing a fiber-reinforced ceramic roller according to claim 6, characterized in that: The melting temperature of the elemental silicon is 1410-1600°C.

9. The method for preparing a fiber-reinforced ceramic roller according to claim 6, characterized in that: The temperature at which the molten silicon forms silicon vapor is 1700° C. to 1800° C.

10. The method for preparing a fiber-reinforced ceramic roller according to claim 1, characterized in that: The method for preparing the silica fiber also satisfies at least one of the following conditions: S9, the dispersant includes at least one of polycarboxylic acid amine, sodium polyacrylate, methyl cellulose and polyvinyl alcohol; S10, the binder is an organic binder, and the organic binder includes at least one of phenolic resin, polypyrrolidone and carboxymethyl cellulose; S11, the solvent includes water; S12, the vacuum degree of the vacuum extrusion molding is 0.01~0.09MPa, and the extrusion force is 5~30MPa; S13, the pressure of the cold isostatic pressing is 120-240 MPa, and the holding time is 10-60 s; S14, the drying temperature is 60-120°C, and the drying time is 12-48h; S15. The sintering is hanging sintering, the sintering temperature is 1400-1800° C., and the holding time is 5-10 hours.

11. A fiber-reinforced ceramic roller produced by the method for producing a fiber-reinforced ceramic roller according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Method for in-situ synthesizing mullite whisker self-toughened mullite ceramics

    CN106747541A

  • Wear-resistant high-performance ceramic roller and preparation method thereof

    CN113004027A

Cited By

  • Preparation method of aluminum oxide ceramic material with high length-diameter ratio and small diameter

    CN121318414A